ALMEIDA, Carla Berenice Starling de. Medicina mestiça: saberes e práticas curativas nas Minas Setecentistas. São Paulo: Annablume, 2010, 184 p. ISBN 978-85-391-0072-9 (Cadernos de Pesquisa do CDHIS, 2014)
sem resumo